Does Local Anesthetic Stereoselectivity or Structure Predict Myocardial Depression in Anesthetized Canines?. Issue 5 (1st September 2002) - Groban, Leanne; Deal, Dwight D.; Vernon, Jason C.; James, Robert L.; Butterworth, John
Abstract : Background and Objectives: It is unclear whether the susceptibility to myocardial depression from an accidental intravascular local anesthetic (LA) administration is associated with LA stereoselectivity or structure. By using direct left ventricular pressure monitoring and echocardiographic indices of contractile function in anesthetized, ventilated dogs, we compared the cardiac depressant effects of bupivacaine, ropivacaine, levobupivacaine, and lidocaine. Methods: Open-chest dogs were randomized to receive escalating incremental infusions of the 4 local anesthetics until cardiovascular collapse. We assumed a concentration relationship for potency of 4:1 for lidocaine/bupivacaine, ropivacaine, and levobupivacaine. Results: All LAs produced concentration-dependent increases in left ventricular end diastolic pressure (LVEDP) and decreases in dP/dtmax, ejection fraction % (EF), fractional shortening (%) (FS), and cardiac output (CO). When comparing the long-acting agents, the effect was least for ropivacaine. The effective concentration estimates for ropivacaine that produced 35% reductions in dP/dtmax and FS were 4.0 μg/mL (95% confidence intervals [CI95 ]: 3.1 to 5.2 μg/mL) and 3.0 μg/mL (CI95 : 2.1 to 4.2 μg/mL), respectively. The concentrations of levobupivacaine that produced these same end points of contractile dysfunction were significantly less: 2.4 μg/mL (CI95 : 1.9 to 3.1 μg/mL) and 1.3 μg/mL (CI95 : 0.9 to 1.8 μg/mL), respectively, and these were not different from bupivacaine. As expected, the concentrations of lidocaine that produced 35% reductions in dP/dtmax and FS were significantly greater than the longer acting agents; 8.0 μg/mL (CI95 : 5.7 to 11.0 μg/mL) and 5.5 μg/mL (CI95 : 3.5 to 8.7 μg/mL), respectively. Conclusions: This study suggests that smaller molecular size and possibly a piperidine-free structure as opposed to stereoselectivity may be the more important factor in reducing the risk of LA-induced myocardial depression.